2021
DOI: 10.2147/phmt.s316194
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Equity and Coverage in Mass Drug Administration for Soil-Transmitted Helminth Infections among School-Age Children in the Hard-to-Reach Setting of Southern Ethiopia

Abstract: Background: Soil-transmitted helminth (STH) infections are prevalent in most developing countries, including Ethiopia, with school-age children (SAC) at high risk of infection. In Ethiopia, despite substantial progress being made on mass drug administration (MDA) coverage for STH infections, its implementation is facing challenges in hard-to-reach areas. This study thus aimed at assessing equity and coverage in MDA and identifying factors associated with drug coverage for STH infections among SAC in the hard-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…However, the coverage in the intervention area for the OSCs was poor, and it was poorer still in the control area. Other authors reported similar findings from Bangladesh [ 9 , 12 , 16 ] and Ethiopia [ 14 ]. Given that SGCs are frequently the primary target of deworming programs, and there is a lack of protocol to integrate the OSCs [ 9 ], it is unsurprising that coverage is higher among the SGCs.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…However, the coverage in the intervention area for the OSCs was poor, and it was poorer still in the control area. Other authors reported similar findings from Bangladesh [ 9 , 12 , 16 ] and Ethiopia [ 14 ]. Given that SGCs are frequently the primary target of deworming programs, and there is a lack of protocol to integrate the OSCs [ 9 ], it is unsurprising that coverage is higher among the SGCs.…”
Section: Discussionsupporting
confidence: 79%
“…On the other hand, the reported coverage for SGCs and OSCs was significantly lower than the nationally reported coverage [ 8 ]. Previous research has found that reporting by pill distributors can sometimes result in over-reporting [ 9 , 14 ]. Because few informal educational institutions are listed in the local registry, those children are often excluded from school-based deworming [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bioethics research on MDA with antibiotics—especially when applied to reduce childhood mortality—is limited. Although ethical issues have been explored in other contexts, such as MDA for seasonal malaria chemoprophylaxis [ 30 ] or soil-transmitted helminths [ 31 ], MDA for childhood mortality is arguably distinct. To our knowledge, no empirical studies describe how critical decision-makers think about ethical concerns in MDA of antibiotics.…”
Section: Introductionmentioning
confidence: 99%